Competencias sociales y tecnologías de la información y la comunicación como factores asociados al desempeño en estudiantes de básica primaria con experiencia de desplazamiento forzado (2015)
The main goal of this paper is to describe the main theoretical framework and findings from the relational analysis of social skills, attitudes to ICT and academic performance reports from a sample made up of teachers (n=9), parents (n=60) and students (n=60) in two elementary schools in the cities of Malambo and Barranquilla, Colombia, who have experienced forced displacement. To this end, a protocol consisting of an informed consent form, the Attitudes towards ICT Questionnaire, the School Conflict Settlement Scales, the MESSY scale for Students and Teachers, a School Behavior Observation Inventory, a Sociodemographic Characterization Questionnaire and a Perception on the use of ICT for parents scale. Results reflect a positive attitude towards the use of ICT on students and teachers, the use of conflict resolution strategies related to exposure to bullying, a higher level of recognition of prosocial behaviors compared with the report on aggressive behavior on the part of teachers and the establishment of statistically significant associations between social skills and prosocial conflict resolution in direct proportion, unlike the inverse relationship between aggressive behavior and prosocial behavior, as well as a directly relationship proportional between prosocial behavior and academic performance and a statistically significant association between the use of ICT and academic performance .